First investigations of an ice core from Eisriesenwelt cave (Austria) - May, Barbara Luise; Spötl, C.; Wagenbach, Dietmar; Dublyansky, Y.; Liebl, J. (The Cryosphere, 2011)
Investigations into the genesis and dynamical properties of cave ice are essential for assessing the climate significance of these underground glaciers. We drilled an ice core through a 7.1 m-thick ice body filling a large cavern of the dynamic ice cave Eisenriesenwelt (Austria). In addition to visual core inspections, quasi-continuous measurements at 2 cm resolution comprised particulate matter, stable water isotope (δ18O, δD) and electrolytic conductivity profiles supplemented by specifically selected samples analyzed for tritium and radiocarbon. We found that recent ablation led to an almost complete loss of bomb-derived tritium removing any ice accumulated since, at least, the early fifties leaving the actual ice surface even below the natural tritium level. The small particulate organic masses rendered radiocarbon dating inconclusive, though a crude estimate gave a basal ice age in the order of several thousand years. The visual stratigraphy and all investigated parameters showed a clear dichotomy between the upper 2 m and the bottom 3 m of the core, which points to a substantial change in the ice formation process. Main features of the core comprise the changing appearance and composition of distinct cryocalcite layers, extremely low total ion content and a surprisingly high variability of the isotope signature. Co-isotope evaluation (δ18O, δD) of the core in comparison with data from precipitation and karst spring water clearly indicate that ice formation is governed by (slow) freezing of dripping water.
Gesehen am 12.08.2022